Germanene/2D-SiC van der Waals heterobilayer: Structural features and tunable electronic properties. (March 2021) - Islam, Md. Sherajul; Mojumder, Md. Rayid Hasan; Ferdous, Naim; Park, Jeongwon
Abstract: Van der Waals heterobilayer, consisting of different two-dimensional (2D) materials, has recently drawn substantial research attention. We present a detailed investigation of the structure and electronic properties of germanene and 2D silicon carbide (Ge/2D-SiC) van der Waals heterobilayer by means of first-principles calculations under the framework of density functional theory. Three different stacking patterns are predicted for this Ge/2D-SiC heterostructure. All the representative structures offer a direct bandgap of approximately 80–100 meV. The breaking of the sub-lattice symmetry as well as the transfer of charges are perceived as the pivotal effects that open the bandgap for each structure. The compressive bi-axial strain is applied for the further tune of the bandgap, resulting in an alter in the bandgap from 85 to 118 meV. Upon varying the interlayer distance between germanene and 2D-SiC the bandgap can further be tuned. The distribution of space charges of the conduction and valence bands and projected density of states represent that germanene plays the main role in forming the heterobilayers electronic properties, thus suggesting the ability of 2D-SiC as a stable substrate. These outcomes expose that Ge/2D-SiC heterostructure would be an incredible resource for imminent Ge-based high-performance nanoelectronic devices such as quantum computing spintronic devices and nanoscale energy storage devices.